Finland - Spanier, Kristine (All around the world., 2022)
"In this book, readers will learn about the unique and defining features of Finland. Vibrant, full-color photos and carefully leveled text will engage young readers as they learn more about the key details of the country, including geography, climate, culture, and resources. Compelling questions encourage further inquiry. Includes reading tips for teachers and parents, a map, quick facts, a table of contents, a glossary, and an index."--